Anatomical Variation of Age-Related Changes in Vertebral Bone Marrow Composition Using Chemical Shift Encoding-Based Water–Fat Magnetic Resonance Imaging - Baum, Thomas; Rohrmeier, Alexander; Syväri, Jan; Diefenbach, Maximilian N.; Franz, Daniela; Dieckmeyer, Michael; Scharr, Andreas; Hauner, Hans; Ruschke, Stefan; Kirschke, Jan S.; Karampinos, Dimitrios C. (Frontiers in Endocrinology, 2018)
Assessment of vertebral bone marrow composition has been proposed as imaging biomarker for osteoporosis, hematopoietic and metabolic disorders. We investigated the anatomical variation of age-related changes of vertebral proton density fat fraction (PDFF) using chemical shift encoding-based water–fat MRI. 156 healthy subjects were recruited (age range 20-29 years: 12/30 males/females; 30-39: 15/9; 40-49: 4/14; 50-59: 9/27; 60-69: 5/19; 70-79: 4/8). An eight-echo 3D spoiled gradient-echo sequence at 3T MRI was used for chemical shift-encoding based water–fat separation at the lumbar spine. Vertebral bodies of L1-L4 were manually segmented to extract PDFF values at each vertebral level. PDFF averaged over L1-L4 was significantly (p<0.05) higher in males than females in the Twenties (32.0±8.0% vs. 27.2±6.0%) and Thirties (35.3±6.7% vs. 27.3±6.2%). With increasing age females showed an accelerated fatty conversion of the bone marrow compared to men with no significant (p>0.05) mean PDFF differences in the Forties (32.4±8.4% vs. 34.5±6.8%) and Fifties (42.0±6.1% vs. 40.5±9.7%). The accelerated conversion process continued resulting in greater mean PDFF values in females than males in the Sixties (40.2±6.9% vs. 48.8±7.7%; p=0.033) and Seventies (43.9±7.6% vs. 50.5±8.2%; p=0.208), though the latter did not reach statistical significance. Relative age-related PDFF change from the Twenties to the Seventies increased from 16.7% (L1) to 51.4% (L4) in males and 76.8% (L1) to 85.7% (L4) in females. An accelerated fatty conversion of bone marrow was observed in females with increasing age particularly evident after menopause. Relative age-related PDFF changes showed an anatomical variation with most pronounced changes at lower lumbar vertebral levels in both sexes.